2006
DOI: 10.1038/sj.ijo.0803291
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between short sleeping hours and childhood overweight/obesity: results from the ‘Québec en Forme’ Project

Abstract: Objective: To assess the relationship between short sleep duration and obesity-related variables in children involved in the 'Québec en Forme' Project. Design: Cross-sectional study. Subjects: A total of 422 children (211 boys and 211 girls) aged between 5 and 10 years from primary schools in the City of Trois-Rivières (Québec) were selected to participate in this study. Measurements: Body weight, height and waist circumference were measured. The children were classified as normal, underweight, overweight or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
220
8
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(260 citation statements)
references
References 24 publications
25
220
8
7
Order By: Relevance
“…53 Thus, the dramatic increase in the incidence of obesity and type 2 diabetes seems to have developed over the same period of time as the progressive decrease in self-reported sleep duration. [54][55][56] A growing body of epidemiological evidence supports an association between short sleep duration and the risk of obesity [57][58][59][60][61] and type 2 diabetes. [62][63][64][65][66] The potential mechanisms by which sleep deprivation may predispose to obesity are: (1) an alteration of the neuroendocrine control of appetite characterized by a decrease in the levels of the anorexigenic hormone leptin and an increase in the levels of the orexigenic hormone ghrelin; (2) an increased opportunity to eat; (3) an altered thermoregulation; and (4) an increased fatigue leading to reductions in physical activity.…”
Section: Short Sleep Duration: Association With Glucose Homeostasismentioning
confidence: 99%
“…53 Thus, the dramatic increase in the incidence of obesity and type 2 diabetes seems to have developed over the same period of time as the progressive decrease in self-reported sleep duration. [54][55][56] A growing body of epidemiological evidence supports an association between short sleep duration and the risk of obesity [57][58][59][60][61] and type 2 diabetes. [62][63][64][65][66] The potential mechanisms by which sleep deprivation may predispose to obesity are: (1) an alteration of the neuroendocrine control of appetite characterized by a decrease in the levels of the anorexigenic hormone leptin and an increase in the levels of the orexigenic hormone ghrelin; (2) an increased opportunity to eat; (3) an altered thermoregulation; and (4) an increased fatigue leading to reductions in physical activity.…”
Section: Short Sleep Duration: Association With Glucose Homeostasismentioning
confidence: 99%
“…6,7 The most probable sleep factor linked with obesity is sleep duration. Cross-sectional evidence suggests an association between short sleep and obesity in children [8][9][10][11] and in young adults. [12][13][14][15] In addition, two prospective cohort studies have shown that short sleep predicts future weight gain in young adults 16 and in middle-aged women.…”
Section: Introductionmentioning
confidence: 99%
“…1 The increase in childhood obesity has developed over the same time period as the progressive decrease in self-reported sleep duration. 2,3 Several crosssectional studies reported on an inverse relationship between body mass index (BMI) and sleep duration during childhood [4][5][6][7][8][9] ; some reported a curvilinear relationship between BMI and sleep duration. 10,11 Additionally, short sleep duration in children was related to insulin resistance, a larger body fat percentage, a larger waist circumference, decreased physical activity and increased television watching.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polymorphisms of the FTO gene (rs9939609) and parental BMI's were determined, since they might be potential confounders as has been shown in previous studies. 9,17,[24][25][26][27] Subjects and methods…”
Section: Introductionmentioning
confidence: 99%